Assessment criteria for ecological and geological zoning of territories - I. I. Kosinova; O. G. Fonova; S. I. Fonova (Юг России: экология, развитие)
Aim. Development of new approaches to ecological and geological zoning of territories based on an integrated assessment of the state of abiotic and biotic components of the environment.Material and Methods. The methodology of teratological analysis of leaf blades is presented, which makes it possible to determine the morphological deformation of vegetational elements associated with external negative influences.Results. The degree of comfort of the environment, as determined by a set of quantitative indicators, is emphasised. The process of generalization of the entire body of information is embodied through the creation of a map of ecological‐geological zoning by combining and "scanning" individual thematic maps using overlays. The legend, as the basis for the logical classification of the map of ecological and geological zoning, fixes its object, subject and defines the semantics.Conclusion. Practical recommendations for the construction of maps of ecological‐geological zoning within the framework of the proposed methodology are presented through the example of large enterprises engaged in petroleum product logistics.